MODERN LEXICOGRAPHIC APPROACHES IN BILINGUAL DICTIONARY COMPILATION - Usakhov, Rustem Muratovich (SCIENCE and SOCIETY, 2026)
The article analyzes lexicographic relations in the creation of a modern bilingual dictionary. The study considers the integration of functional-systemic, typological-cognitive and translation-communicative components, as well as strategies for connecting national materials on the Karakalpak language.
Keywords: bilingual dictionary; lexicography; language and culture; semantics; cognitive approach; pragmatics; national-cultural unity; linguocultural science